Streptococcus pneumoniae Type 1 Pilus – A Multifunctional Tool for Optimized Host Interaction - Ness, Stefan; Hilleringmann, Markus (Frontiers in Microbiology, 2021)
Streptococcus pneumoniae represents a major Gram-positive human pathogen causing bacterial pneumonia, otitis media, meningitis and other invasive diseases. Several pneumococcal isolates show increasing resistance rates against antibacterial agents. A variety of virulence factors promote pneumococcal pathogenicity with varying importance in different stages of host infection. Virulence related hair-like structures (“pili”) are complex, surface located protein arrays supporting proper host interaction. In the last two decades different types of pneumococcal pili have been identified: Pilus-1 (P1) and pilus-2 (P2) are formed by the catalytic activity of sortases that covalently assemble secreted polypeptide pilin subunits in a defined order and finally anchor the resulting pilus in the peptidoglycan. Within the long pilus fiber the presence of intramolecular isopeptide bonds confer high stability to the sequentially arranged individual pilins. This mini review will focus on Streptococcus pneumoniae TIGR 4 P1 molecular architecture, the subunits it builds and provides insights into P1 sortase-mediated assembly. The complex P1 architecture (anchor-/backbone-/tip-subunits) allows the specific interaction with various target structures facilitating different steps of colonization, invasion and spreading within the host. Optimized pilin subunit confirmation supports P1 function under physiological conditions. Aspects of P1- host interplay are summarized, including recent insights into P1 mechanobiology, which have important implications for P1 mediated pathogenesis.